Micro-CT Evaluation of Root Canal Transportation and Centering Ability in Mesial Canals of Mandibular First Molars - Ince Yusufoglu, Selen; Saricam, Esma; Ocak, Mert; Geneci, Ferhat; Bilecenoğlu, Burak (Journal of Dentistry Indonesia, 2026)
Background: This study aimed to evaluate canal transportation, centering ability, structure model index (SMI), surface area, and root canal volume changes in the mesial canals of mandibular first molars using micro-CT. Methods: Twenty-four mandibular first molars with two separate mesial canals and moderate curvature were included. Teeth were scanned using micro-CT before instrumentation and randomly divided into three groups (N = 8). Root canals were prepared using OneShape, OneCurve, and Rotate file systems, followed by post-instrumentation micro-CT scanning (10µm/pixel resolution). Changes in canal volume, surface area, transportation, centering ability, and SMI were analyzed at the apical, middle, and coronal thirds. Data were statistically evaluated (p < 0.05). Results: Canal transportation was significantly greater in the middle third compared to the apical and coronal regions. OneCurve (0.06 ± 0.02) and OneShape (0.09 ± 0.05) systems showed significantly higher transportation than the Rotate system (p < 0.05). No significant differences were observed among the groups in centering ability (p > 0.05), although the Rotate system demonstrated better centering ability. Additionally, the OneShape system resulted in greater increases in canal volume and SMI. Conclusions: While OneShape and OneCurve systems exhibited similar transportation, the Rotate system provided more favorable shaping outcomes. OneShape caused greater dentin removal and morphological changes.